2020
DOI: 10.3390/jmse8040289
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Extreme Wave Conditions for Wave Energy Converter Design and Project Risk Assessment

Abstract: Best practices and international standards for determining n-year return period extreme wave (sea states) conditions allow wave energy converter designers and project developers the option to apply simple univariate or more complex bivariate extreme value analysis methods. The present study compares extreme sea state estimates derived from univariate and bivariate methods and investigates the performance of spectral wave models for predicting extreme sea states at buoy locations within several regional wave cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…This is an indication that the bulk of the data is represented reasonably well by the model at these two locations, whereas the extremes (high H s ) are not, which is a known issue for this hindcast data [36]. As noted in Section 1, Neary et al [30] reported, on the other hand, a hindcast underestimation of sea states with high H s along the environmental contours for their study sites. However, differences in wave climate, hindcast models, and contour method makes a direct comparison difficult.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This is an indication that the bulk of the data is represented reasonably well by the model at these two locations, whereas the extremes (high H s ) are not, which is a known issue for this hindcast data [36]. As noted in Section 1, Neary et al [30] reported, on the other hand, a hindcast underestimation of sea states with high H s along the environmental contours for their study sites. However, differences in wave climate, hindcast models, and contour method makes a direct comparison difficult.…”
Section: Discussionmentioning
confidence: 87%
“…Such considerations further highlight the importance of understanding and characterizing extreme sea states. A recent publication by Neary et al [30] compared environmental contours for buoy observations and different hindcast data sets for several locations on the West Coast and East Coast of USA with a focus on extreme sea states for WEC applications. They employed the I-FORM with PCA to estimate environmental contours, and found that the model data generally lead to smaller contours compared with those from observations and that estimates of extreme sea states with high H s were underestimated by the models.…”
Section: Global Atmospheric Reanalysis Datamentioning
confidence: 99%
“…In the framework of wave resource assessment studies, data validation, variability and uncertainty measures, and analysis of extreme waves should also be included. See, e.g., [4,[19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The three major obstacles of the industrialization of WECs are associated with reliability, efficiency, and economic viability, but extensive efforts are being spent on the improvement of these aspects [8]. Reliability is achieved by refining the WEC designs and optimizing control strategies [9,10], while economic viability and efficiency require the optimal selection of the site, the system, and materials in order to reduce costs and environmental impact while guaranteeing maximum energy absorption [11,12].…”
Section: Introductionmentioning
confidence: 99%